Dietary modulation of gut microbiota and its role in atopic dermatitis: integrative evidence from animal and human studies - Xu, Fang; Jiang, Xinyue; Jin, Yuyang; Yang, Yadi; Chen, Xinyue; Chen, Ying (Frontiers in Immunology, 2025)
BackgroundAtopic dermatitis (AD) is associated with disturbance in the gut microbiota, but the dietary factors behind this dysbiosis are still unknown. Therefore, we investigated how food choice patterns impact the gut microbiota, which in turn influences the development and progression of AD.MethodsA mice AD model washed using 2,4-dinitrochlorobenzene (DNCB). After 4 weeks, epidermal histopathology, serum immunoglobulin E (IgE) levels, and gut microbiota profiles were assessed. At the same time, we recruited 102 clinically diagnosed AD patients and 102 age- and sex-matched controls. Participants completed a food frequency questionnaire and provided stool samples to analyze dietary patterns, gut microbiota diversity, composition, function, and their associations.ResultsIn mice, AD induction caused marked epidermal thickening, inflammatory infiltration, and a dose-dependent increase in serum IgE (up to ~3.0-fold compared to control, p < 0.01). Alpha diversity analysis revealed a significantly higher ACE index in the high-dose group (p < 0.05), whereas the Chao, Shannon, and Simpson indices did not exhibit significant changes. In humans, microbial diversity declined markedly (Shannon index, −20%, p < 0.001), with reductions in Firmicutes and Bacteroidota, but enrichment in Actinobacteriota and Bifidobacterium. Dietary patterns in AD patients showed lower consumption of refined grains (-24 g/day) and higher intake of vegetables and fruits (+38 g/day), which strongly correlated with microbial shifts. Functional predictions revealed reduced carbohydrate, amino acid, and energy metabolism pathways. Together, these findings suggest a novel diet–microbiota–immune axis in the pathogenesis of AD.ConclusionsEvidence from mice to humans suggests that reduced intake of refined grains and increased consumption of plant-based foods are associated with remodeling of the gut ecosystem – including reduced diversity and metabolic capacity – which may play a role in AD. These findings are exploratory and should be considered hypothesis-generating, warranting validation in prospective studies. These findings provide a theoretical and scientific basis for future research on dietary interventions and gut microbiota modulation strategies for preventing and treating AD.